Addressing healthcare barriers faced by asylum seekers and refugees through an interprofessional symposium (Canadian Medical Education Journal, 2023)
Implication StatementIn this work, we describe an interprofessional healthcare symposium driven by the challenges faced by the local asylum-seeking/refugee population in Montreal. McGill University medical, nursing, dietetics, and social work students partnered with local experts to provide attendees with tools to better meet the needs of Montreal’s migrant population. This student-led initiative, unique in its interdisciplinary and comprehensive nature, increased awareness of the needs of an underserved population while promoting student engagement in health advocacy and interprofessional collaboration. It also enhances the development of skills essential to provide culturally sensitive care.